Protocol for a seamless phase 2A-phase 2B randomized double-blind placebo-controlled trial to evaluate the safety and efficacy of benfotiamine in patients with early Alzheimer's disease (BenfoTeam). - Howard H Feldman; José A Luchsinger; Gabriel C Léger; Curtis Taylor; Diane M Jacobs; David P Salmon; Steven D Edland; Karen Messer; Carolyn Revta; Sarah A Flowers; Kerry S Jones; Albert Koulman; et al. (PLoS ONE)
Background Benfotiamine provides an important novel therapeutic direction in Alzheimer's disease (AD) with possible additive or synergistic effects to amyloid targeting therapeutic approaches. Objective To conduct a seamless phase 2A-2B proof of concept trial investigating tolerability, safety, and efficacy of benfotiamine, a prodrug of thiamine, as a first-in-class small molecule oral treatment for early AD. Methods This is the protocol for a randomized, double-blind, placebo-controlled 72-week clinical trial of benfotiamine in 406 participants with early AD. Phase 2A determines the highest safe and well-tolerated dose of benfotiamine to be carried forward to phase 2B. During phase 2A, real-time monitoring of pre-defined safety stopping criteria in the first approximately 150 enrollees will help determine which dose (600 mg or 1200 mg) will be carried forward into phase 2B. The phase 2A primary analysis will test whether the rate of tolerability events (TEs) is unacceptably high in the high-dose arm compared to placebo. The primary safety endpoint in phase 2A is the rate of TEs compared between active and placebo arms, at each dose. The completion of phase 2A will seamlessly transition to phase 2B without pausing or stopping the trial. Phase 2B will assess efficacy and longer-term safety of benfotiamine in a larger group of participants through 72 weeks of treatment, at the selected dose. The co-primary efficacy endpoints in phase 2B are CDR-Sum of Boxes and ADAS-Cog13. Secondary endpoints include safety and tolerability measures; pharmacokinetic measures of thiamine and its esters, erythrocyte transketolase activity as blood markers of efficacy of drug delivery; ADCS-ADL-MCI; and MoCA. Conclusion The BenfoTeam trial utilizes an innovative seamless phase 2A-2B design to achieve proof of concept. It includes an adaptive dose decision rule, thus optimizing exposure to the highest and best-tolerated dose. Trial registration ClinicalTrials.gov identifier: NCT06223360, registered on January 25, 2024. https://classic.clinicaltrials.gov/ct2/show/NCT06223360.